Aspectos geomorfológicos del sector medio e inferior de la Pampa Deprimida, provincia de Buenos Aires - Fucks, Enrique (2012)
The Llanura Pampeana (Pampean Plains) is a geomorphological realm which is currently dominated by warm and humid climatic conditions, which promote almost exclusively, chemical weathering and fluvio-lacustrine processes. These are very contrasting with those processes developed in previous periods in which arid and semiarid conditions left the most conspicuous records. In the western sector of the Buenos Aires province, the Pampa Arenosa (Sandy Pampa) is developed, where longitudinal, parabolic and blowout, currently stabilized dunes, can be recognized. These features reflect extremely arid conditions. On the Coastal Plain, the littoral area of the Río de la Plata and the Atlantic Ocean, the topography is flat with wide flooded areas formed by lagoons, non-functional tidal channels, littoral barriers and dunes, associated with the post-glacial marine ingression of the Oxygen Isotopic Stage (MSI) 1. In this area, older records of high sea level can be also recognized. Between both areas, the Pampa Deprimida (Depressed Pampa) is developed. This is an elongate NW-SE depression with the Salado river as main collector and a large number of lagoons, some of which are silted. These lagoons are developed in deflation basins generated or re-activated at different times when climatic conditions were more arid. Lunettes are developed mostly on the NE sector. Stratigraphic survey at different sites of the Salado River showed fluvial deposits that ranged from the end of the late Pleistocene to the Holocene, with numerical ages from 13.400 ± 200 14C years BP to 680 ± 60 14C years BP. The origin of the depression of the Salado River is related to a combination of processes, in which physical-chemical weathering and deflation produced the gradual excavation of the landscape. Weathering was localized in some cases, producing deflation basins associated with lunettes. These processes where inhibited when warm-temperate conditions prevailed, triggering the fluvial processes which gradually silted the whole depression. The lagoons developed on the Salado River valley are in process of silting, while those located away from the main valley show minor changes in their shaping because of lesser sedimentary supply.